Hollow copper–ceria microspheres with single and multiple shells for preferential CO oxidation. Issue 23 (28th May 2019) - Yu, Xie; Wu, Jinfang; Zhang, Aiai; Xue, Lei; Wang, Qi; Tian, Xiaopeng; Shan, Shiyao; Zhong, Chuan-Jian; Zeng, Shanghong
Abstract : The triple-shelled CuO/CeO2 exhibits superior catalytic performance for CO-PROX due to its fine-tunable geometric and electronic interactions. Abstract : The architecture of catalyst particles plays an important role in determining the catalytic properties. However, the challenge is the ability to tune the architecture on a nanoscale. Herein, we report the design and construction of hollow CuO/CeO2 microspheres with controllable shells, which exhibit significantly enhanced catalytic performance. The hollow CuO/CeO2 microspheres with single and multiple shells were synthesized by a self-templating method. The catalytic activity of the catalysts for preferential CO oxidation is shown to increase with increasing the number of the spherical shells. A maximum performance is observed for the triple-shelled catalyst, reaching a CO conversion of 100% and CO2 selectivity of 91% at 95 °C. The triple-shelled catalyst also displays a broad temperature window for CO total conversion from 95 °C to 195 °C. The findings are attributed to the enhanced exposure of the active sites on the surface of the triple-shelled architecture, fine-tunable geometric and electronic interactions, and increased space inside the catalyst, which together amplify the reactant access and interaction.